Structural Basis for the Function of the β-Barrel Assembly-Enhancing Protease BepA. Issue 3 (1st February 2019) - Shahrizal, Mohammad; Daimon, Yasushi; Tanaka, Yoshiki; Hayashi, Yugo; Nakayama, Shintaro; Iwaki, Shigehiro; Narita, Shin-ichiro; Kamikubo, Hironari; Akiyama, Yoshinori; Tsukazaki, Tomoya
Abstract: The β-barrel assembly machinery (BAM) complex mediates the assembly of β-barrel membrane proteins in the outer membrane. BepA, formerly known as YfgC, interacts with the BAM complex and functions as a protease/chaperone for the enhancement of the assembly and/or degradation of β-barrel membrane proteins. To elucidate the molecular mechanism underlying the dual functions of BepA, its full-length three-dimensional structure is needed. Here, we report the crystal structure of full-length BepA at 2.6-Å resolution. BepA possesses an N-terminal protease domain and a C-terminal tetratricopeptide repeat domain, which interact with each other. Domain cross-linking by structure-guided introduction of disulfide bonds did not affect the activities of BepA in vivo, suggesting that the function of this protein does not involve domain rearrangement. The full-length BepA structure is compatible with the previously proposed docking model of BAM complex and tetratricopeptide repeat domain of BepA. Graphical Abstract: Highlights: Crystal structure (2.6 Å) of full-length BepA, β-barrel assembly-enhancing protease BepA Crystal structure represents both its functional and resting states. Functional model of BepA was proposed.